Why Is Student Deviance Lower in Japan Than in the United States?: Influences of Individual, Parental, Peer, Social, and Environmental Factors - Kobayashi, Emiko (International criminal justice review, 2020)
Drawing on the cultural collectivism-individualism literature, we predict that Japanese students, compared to Americans, tend to commit fewer deviant acts because they are less inclined toward individualistic value orientations, risk seeking, negative emotionality, and subjective stress; because they are exposed to greater parental discipline and have stronger parental attachment; because they have weaker peer attachment and associate with peers who react less favorably to deviance; because they have stronger bonds to conventional society and greater social support from significant others; and because they are exposed to fewer deviance opportunities. Analyses of comparable data from college students in Japan (N = 469) and the United States (N = 594) provided mixed support for our predictions. As expected, Japanese students committed fewer deviant acts during their high school days. Furthermore, consistent with expectations, Japanese students had lower scores on all four individual factors, the two peer factors, and the environmental factor of deviance opportunities. After controlling for these seven factors, the effect of Japan versus the United States decreased by one third. The decrease was not greater at least partly because, in Japan, compared to the United States, risk seeking had significantly less influence on student deviance, and subjective stress had significantly more influence on student deviance.